Impact of pharmacist-led interventions on diabetes management at a community pharmacy in Pakistan: a quasi-experimental study - Muhammad Abubakar; Aiesha Ishaque; Faisal Shahzad; Muhammad Atif; Tabinda Ashfaq (Journal of the Pakistan Medical Association, 2021)
Published in August 2021